In What Sense Is Theistic Evolution More Rational Than Naturalistic Evolution? - Bylica, Piotr (Studia Philosophiae Christianae, 2025)
Drawing on the contributions of logical positivism and the socio-historical perspective in the philosophy of science, I advocate the thesis of the empirical equivalence between metaphysical theistic and naturalistic interpretations of the evolutionary process. This process, defined by the variability of life forms on Earth, primarily occurs through natural selection and genetic mutations. Highlighting the shared aspects of the anti-naturalist arguments put forward by Clive S. Lewis and Alvin Plantinga, I propose that these arguments support the view that a theistic interpretation of evolution is more rational than a naturalistic one. This is because naturalistic evolutionism encounters the problem of its own credibility, as it calls into question the reliability of our cognitive faculties. In contrast, theistic interpretations of evolution are more compatible with the reliability of our cognitive faculties. ---------------------------------------- Zgłoszono: 23/07/2025. Zrecenzowano: 25/08/2025. Zaakceptowano do publikacji: 9/10/2025.